2020
DOI: 10.1111/apha.13458
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disordered breathing in pregnancy: A review of the pathophysiology of adverse pregnancy outcomes

Abstract: Sleep disordered breathing (SDB) is a common obesity-related co-morbidity with strong associations to cardiometabolic disease. The risk of SDB is increased during pregnancy, particularly among obese pregnant women. Accumulating evidence suggests that an association exists between maternal SDB and the development of adverse pregnancy outcomes, particularly gestational diabetes and hypertensive disorders of pregnancy. Intermittent hypoxia, a central characteristic of SDB, has been shown in animal and clinical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 124 publications
(170 reference statements)
0
19
0
3
Order By: Relevance
“…Johns et al 21 reviewed the phenomenon in younger, pregnant women, in whom an association exists between maternal sleep-disordered breathing and adverse pregnancy outcomes via a potential dysregulation of several biological pathways. 22 Another pregnancy-related complication was recently investigated in depth by Pospelov et al, showing endogenous brainsparing responses in brain pH and PO2 in a rodent model of birth asphyxia. 23 Insufficient oxygen availability is, however, not exclusively a pathological phenomenon.…”
Section: Environment and Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Johns et al 21 reviewed the phenomenon in younger, pregnant women, in whom an association exists between maternal sleep-disordered breathing and adverse pregnancy outcomes via a potential dysregulation of several biological pathways. 22 Another pregnancy-related complication was recently investigated in depth by Pospelov et al, showing endogenous brainsparing responses in brain pH and PO2 in a rodent model of birth asphyxia. 23 Insufficient oxygen availability is, however, not exclusively a pathological phenomenon.…”
Section: Environment and Exposurementioning
confidence: 99%
“…In a rodent model of sleep apnoea, Laouafa et al showed a protective role of female sexual hormones against several components of sleep apnoea pathophysiology, including mitochondrial dysfunction, with potential therapeutic implications for menopausal patients. Johns et al 21 reviewed the phenomenon in younger, pregnant women, in whom an association exists between maternal sleep‐disordered breathing and adverse pregnancy outcomes via a potential dysregulation of several biological pathways 22 . Another pregnancy‐related complication was recently investigated in depth by Pospelov et al, showing endogenous brain‐sparing responses in brain pH and PO2 in a rodent model of birth asphyxia 23 .…”
mentioning
confidence: 99%
“…3,4 However, a rather large knowledge gap remains. 5 Johns et al 6 shed light on pregnancy-related sleep disordered breathing (SDB), an obesity-related disorder associated with cardiometabolic disease and the development of adverse pregnancy outcomes, such as hypertension and gestational diabetes. In obese mothers, the relative inability of myometrial arteries to relax due to a deficit in endothelial calcium signalling contributes to an inability to recover following compression during contractions, which might contribute to perinatal complications in obese mothers.…”
Section: Pregnancymentioning
confidence: 99%
“…Prevalence of OSA in the general population, generally higher in men, increases in parallel with the obesity rate (Heinzer et al., 2015). While young females are generally at lower risk for OSA, anatomical and hormonal changes during pregnancy may predispose women to either a new development or worsening of the pre‐existing OSA (Johns et al., 2020). Obesity seems to be a risk factor for OSA during pregnancy, similar to the non‐pregnant population.…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent hypoxia leads to increased sympathetic neural activity, oxidative stress, systemic inflammation, and activation of hypothalamic–pituitary–adrenal (HPA) axis. These mechanisms predispose individuals to hypertension, DM, and cardiovascular disease (Heinzer et al., 2015; Johns et al., 2020; Reutrakul & Mokhlesi, 2017; Wang et al., 2013). While the mechanistic studies in pregnant population are scarce, small studies showed that sleep disruption was associated with elevated serum tumour necrosis factor‐α (TNF‐α) (Okun et al., 2007), and that OSA was related to blunted cortisol awakening response (Bublitz et al., 2018).…”
Section: Introductionmentioning
confidence: 99%